# Factorise by splitting the middle term method 2 - a - a square

2
by ananya1

2015-02-08T12:53:33+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
given, 2-a-a² = 0
it can be written as      a²+a-2=0
a²+2a-a-2=0
a(a+2)-1(a+2)=0
(a-1)(a+2)=0
a-1=0  or  a+2=0
a=1  or   a=-2
Thank you so much
u r welcome
The given question has no equation but expression. Why did you find the roots. Its only expression. which needs to be factorised.
no she had already said to me in b4 question that she want them
2015-02-09T16:01:59+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
2 - a - a²
⇒2 - 2a + a - a²
⇒ 2(1 - a) + a(1 - a)
⇒ (1 - a)(2 + a)